On studious philosopohy of (higher) education? - Waghid, Y. (South African Journal of Higher Education, 2022)
Over a decade my reading of Giorgio Agamben’s writings on philosophy in relation to politics, aesthetics, and religion revolved around how notions of infancy, (im)potentiality, becoming, community, rhythmic and kairotic action can guide an understanding of higher education. Although Agamben has not written specifically about education the above concepts can be recognised as significant to a theory of higher education particularly because his ideas invariably radicalise any understanding of higher education. Such a radicalisation of higher education involves thinking anew about higher education that remains unfinished or what Igor Jasinki (2018) refers to as “education without ends”. In this article, I offer a way of how to think differently about a philosophy of higher education concerning the notion of “education without ends” and in reference to Agamben’s (1985) idea of studious play.